The Effect Of Durian Peel Extract (Durio zibethinus Murr.) Against Fall Armyworm (Spodoptera frugiperda) - Abdurrasyid, Zaki Amarullah; Syahputra, Edy; Ramadhan, Tris Haris (CROPSAVER, 2025)
Durian peel is one of the agricultural wastes that has the potential to become a valuable product if processed properly. It contains secondary metabolites such as phenols, alkaloids, tannins, and saponins. These compounds can be utilized as active ingredients in the formulation of botanical insecticides. However, there have been no reports on the use of durian rind as a base material for botanical insecticide production, thus necessitating a study to determine the effect of durian rind extract on test insects, particularly the fall armyworm (Spodoptera frugiperda). This study also aims to investigate the effects of various concentrations of durian rind extract on the mortality of S. frugiperda. The research was conducted from September 2023 to December 2024 at the Pesticide Laboratory of Universitas Tanjungpura. The study employed a leaf-dipping method using corn leaves and consisted of a preliminary test, advanced test, and antifeedant assay. The antifeedant test was carried out using both choice and no-choice methods with the following concentrations: 0% (control), 0.1% (LC10), 0.4% (LC25), 1.4% (LC50), and 4.6% (LC75). The observed variables included mortality percentage, sex ratio, average pupal weight, average larval weight, number and viability of eggs, and feeding activity of S. frugiperda. The extract at a concentration of 4.6% had a significant effect on the duration of the imago and pupal stages, total eggs per female, and the male sex ratio of S. frugiperda. Durian rind extract requires high concentrations to affect the growth and development of S. frugiperda, thus it is classified as a botanical insecticide with low toxicity.